Utilization Of Information And Communication Technology In Entrepreneurship In Bungbulang Village, Hegarmanah District, Bungbulang - Rosliani, Elin; Nugraha, Yopi; Budiman, Tedi; Rahayu, Dinar; Habil, Rizki; Zia, Halida (Indonesian Journal of Community Empowerment (IJCE), 2024)
The rapid development of information and communication technology (ICT) in efforts to streamline public services needs to be implemented at the village level. ICT can not only enhance services but also be beneficial in data processing, which can be used for development planning, supporting community welfare, and many other benefits. This study aims to identify the readiness for ICT implementation in terms of human resources, infrastructure, institutions, and budget, and to assess the services provided through ICT. The method used is a survey with the research location in Hegarmanah Village, Bungbulang Sub-district, Garut Regency. The findings of this study indicate a limited utilization of technology in marketing products within entrepreneurship.